ANALISIS PERBANDINGAN KINERJA KARYAWAN PERUSAHAAN DAERAH AIR MINUM (PDAM) (STUDI KASUS PDAM TIRTA SIAK DAN TIRTA KAMPAR) - Handoyo, Leonardus Teguh; Zulfadil, Zulfadil; Machasin, Machasin (Jurnal Tepak Manajemen Bisnis, 2019)
This aims of this study is to compare the performance of employees ofthe regional water utility company (PDAM) (case study of PDAM Tirta Siak andTirta Kampar). This research uses primary data, namely data obtained frominterviews and administering questionnaire to all employees of PDAM Tirta Siakand Tirta Kampar. Secondary data obtained relates to the history of the object ofresearch and organizational structure. Th samples size were 93 employees ofPDAM Tirta Siak and 96 employees of PDAM Tirta Kampar. The analyticalmethod used of this research is a multiple liniear regression analysis andindependent sample t-test in the form of spss version 24 program.The results of this study indicate that 1) partially and simultaneouslyleadership, motivation and compensation have a positif and significant effect onthe performance of employees of PDAM Tirta Siak. 2) partially andsimultaneously leadership, motivation and compensation have a positive andsignificant effect on the performance of employees of PADM Tirta Kampar. 3)there is a difference between performance of employess PDAM Tirta Siak andTirta Kampar, the performance of PDAM Tirta Siak is better than PDAM Tirta Kampar.